Knowledge Management best practice in higher learning institution: a systematic literature review - Ismail, Halijah; Abdullah, Rusli (Little Lion Scientific, 2016)
This systematic literature review (SLR) aims to identify the Knowledge Management (KM) Best Practice components in the KM Model proposal for Higher Learning Institutions (HLI) environment. The KM Best Practice components identified from this paper will be referring in the future study to verify the effectiveness of the components to be the best practice for KM. A SLR of KM Best Practice to identify and define the components of Best Practice from the KM models was conducted recently. 179 articles included in the literature review were extracted based on the exclusion criteria and only retained 71 related reviews. The review of published papers of conference and journals’ articles shows the components of Best Practice in KM are basically divided into two aspects which is the soft aspect and the hard aspect. The literature evidence the lacks of combination of these two aspects into an integrated model decelerate KM Best Practice to fully throttle in the organization. The scenario leads to the immaturity of the HLI towards the implementation of KM System. The first steps of identifying the attributes to measure the components from the models in the literature will led to the definition of the KM Best Practice component for the higher learning environment as concluded in this Systematic Literature Review.